실내수영장에 대한 지각된 혜택과 지각된 위험이 감정반응, 강습태도 및 구전의도에 미치는 영향 - 송석록; Sok-rok Song; 정정희; Jung-hee Jung (Ch'eyuk kwahak yŏn'gu, 2019)
[목적] 이 연구의 목적은 실내수영장에 대한 지각된 위험과 지각된 혜택이 감정반응, 강습태도 및 구전의도와의 관계를 구조방정식모형을 통해 실증적으로 검증하는 것이다. [방법] 이를 위해 경기도에 소재한 상업실내수영장 6개소 남녀 회원 224명을 대상으로 설문조사를 실시하였다. 표집방법은 할당표본추출법과 설문지작성은 자기기입식으로 하였다. 제안한 구조모형을 검증하기 위해 IBM SPSSWIN Ver. 23.0과 AMOS 18.0을 사용하였다. [결과] 첫째, 지각된 위험은 긍정적 감정에 부(-)의 영향을 미쳤다. 둘째, 지각된 위험은 부정적 감정에 정(+)의 영향을 미쳤다. 셋째, 지각된 혜택은 긍정적 감정에 정(+)의 영향을 미쳤다. 넷째, 지각된 혜택은 부정적 감정에 부(-)의 영향을 미치지 않았다. 다섯째, 긍정적 감정은 강습태도에 정(+)의 영향을 미쳤다. 여섯째, 부정적 감정은 강습태도에 부(-)의 영향을 미치지 않았다. 일곱째, 긍정적 감정은 구전의도에 정(+)의 영향을 미쳤다. 여덟 번째, 부정적 감정은 구전의도에 부(-)의 영향을 미치지 않았다. 아홉번째, 강습태도는 구전의도에 정(+)의 영향을 미쳤다. [Purpose] The purpose of this research is to empirically analyze the relationship between a indoor swimming pool on perceived risk & perceived benefit, emotion responses, class attitude, and word-of-mouth intention through structural equation model analysis. [Methods] This study set 224 members at the six private indoor swimming pools located in Gyeonggido as the research subjects. As for sampling method, convenience sampling method was used, and self-administered questionnaire was used for the survey. In an effort to verify the proposed structural model, this study used SPSSWIN Ver. 23.0 and AMOS 18.0. [Results] First, perceived risk had a positive effect on positive emotion. Second, perceived risk had a positive effect on negative emotion. Third, perceived benefit had a positive effect on positive emotion. Fourth, perceived benefit did not have a positive effect on negative emotion. Fifth, positive emotion had a positive effect on class attitude. Sixth, negative emotion did not have a positive effect on class attitude. Seventh, positive emotion had a positive effect on word-of-mouth intention. Eighth, negative emotion did not have a positive effect on word-of-mouth intention. Ninth, class attitude had a positive effect on word-of-mouth intention.